2013
DOI: 10.1080/00103624.2012.756508
|View full text |Cite
|
Sign up to set email alerts
|

Boron Requirement of Irrigated Cotton in a Typic Haplocambid for Optimum Productivity and Seed Composition

Abstract: Boron (B) deficiency hampers cotton (Gossypiumhirsutum L.) growth and productivity globally, especially in calcareous soils. The crop is known as a heavy feeder of B; however, its reported plant analysis diagnostic norms for B-deficiency diagnosis vary drastically. In a 2-year field experiment on a B-deficient [hydrochloric acid (HCl)-extractable 0.47 mg B kg −1 ], calcareous, Typic Haplocambid, we studied the impact of soil-applied B on cotton (cv. CIM-473) growth, productivity, plant tissue B concentration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Boron (B) deficiency causes significant losses in cotton production (Ahmed et al, 2013;Bogiani et al, 2014), with crops responding favorably to B fertilization (Bellaloui et al, 2015). Despite a certain resistance to B toxicity in cotton (Ahmed et al, 2008), plant development may also be compromised when grown under high B concentrations (Ahmed et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Boron (B) deficiency causes significant losses in cotton production (Ahmed et al, 2013;Bogiani et al, 2014), with crops responding favorably to B fertilization (Bellaloui et al, 2015). Despite a certain resistance to B toxicity in cotton (Ahmed et al, 2008), plant development may also be compromised when grown under high B concentrations (Ahmed et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cotton has a high B requirement, partially, due to the inherently limited B mobility within cotton plants. Although B was shown to affect yield and seed and fiber quality in cotton, its effects on seed nutrition have not been well investigated [ 3 , 15 , 16 ], especially under water stress [ 3 , 16 ]. It was reported that a level of <20 mg kg -1 is considered deficient level and the range between 20 and 80 mg kg -1 is sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the adequacy range of B in plant tissue is not clearly defined and difficult to interpret [ 15 ]. This complexity of B status in tissue may have led to report that B can be deficient in a number of crops and have significant effect on yield [ 15 , 16 ] and quality [ 15 , 16 ] even when there are no vegetative signs of deficiency and even when B concentration in soil is present at the adequate range [ 15 , 20 , 21 ]. Environmental factors (soil moisture, soil texture, and soil reaction) [ 22 , 23 ], species and cultivar [ 24 ], and cell wall composition that affect B uptake and requirement is also another source of variability determining B nutritional status of cotton plants.…”
Section: Introductionmentioning
confidence: 99%
“…Boron is essential for growth and development, and its deficiency negatively affects the yield and seed nutritional quality of cotton (Ahmed et al, 2011;Ahmed et al, 2013). Boron affects cottonseed composition and nutritional quality through the modulation in uptake and translocation of other nutrients as well (Ahmed et al, 2011;Bellaloui et al, 2015).…”
Section: Introductionmentioning
confidence: 99%